The Influence of Village Apparatus Competence, Information Technology Utilization, Internal Control Systems, and Community Participation on the Accountability of Village Fund Management in Bandar Setia, Deli Serdang - Damayanti, Putri Merry; Nasution, Yenni Samri Juliati; Kusmilawaty, Kusmilawaty (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the extent to which community participation, village apparatus competence, information technology utilization, and internal control mechanisms influence the accountability of village fund management. A quantitative approach was employed, with data collected through a questionnaire. Respondents comprised both community members and village officials residing in Bandar Setia, Deli Serdang. The data were analyzed using multiple linear regression via SPSS software, based on purposive sampling of 50 selected respondents. The findings revealed the following: (1) Community participation significantly affects the accountability of village fund management (t-value = 2.286 > t-table = 2.014; p-value = 0.027 < 0.05); (2) Village apparatus competence has a significant impact (t-value = 2.119 > t-table = 2.014; p-value = 0.040 < 0.05); (3) The use of information technology also significantly influences accountability (t-value = 3.399 > t-table = 2.014; p-value = 0.001 < 0.05); (4) Internal control mechanisms significantly affect village fund accountability (t-value = 2.501 > t-table = 2.014; p-value = 0.016 < 0.05). Based on these findings, it is recommended that village officials strengthen their organizational commitment to foster a sense of ownership and prevent the misuse of village funds for personal gain. This research is limited to 50 respondents in one village. The results indicate that the application of information technology can enhance accountability in managing village funds. Therefore, training and the digitalization of village administration should be a priority for local governments.